2018
DOI: 10.1186/s12859-018-2142-1
|View full text |Cite|
|
Sign up to set email alerts
|

Realizing drug repositioning by adapting a recommendation system to handle the process

Abstract: BackgroundDrug repositioning is the process of identifying new targets for known drugs. It can be used to overcome problems associated with traditional drug discovery by adapting existing drugs to treat new discovered diseases. Thus, it may reduce associated risk, cost and time required to identify and verify new drugs. Nowadays, drug repositioning has received more attention from industry and academia. To tackle this problem, researchers have applied many different computational methods and have used various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…However, therapies against ATC have not been improved [ 25 ]. One approach to accelerate the discovery is by drug repositioning [ 26 ]. In this study, we explored the therapeutic effects by a combination of troglitazone and lovastatin.…”
Section: Discussionmentioning
confidence: 99%
“…However, therapies against ATC have not been improved [ 25 ]. One approach to accelerate the discovery is by drug repositioning [ 26 ]. In this study, we explored the therapeutic effects by a combination of troglitazone and lovastatin.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used drug chemical structures and protein targets data to build a dual regularized one-class collaborative filtering model that surpassed the previously introduced state-of-the-art models. Ozsoy et al [ 119 ] treated the drug repositioning process as a recommendation process and utilized Pareto dominance and collaborative filtering to identify drug-disease associations. The authors integrated multisource drugs data (protein targets, chemical structures, and side effects) and applied a variety of similarity measures to calculate drug–drug similarities and then used a Pareto dominance model to identify neighbor drugs.…”
Section: Computational Drug Repositioning Approachesmentioning
confidence: 99%
“…In order to evaluate the efficiency of potential repositioned drugs, Rakshit et al [ 126 ] introduced a metric called On-Target Ratio (OTR) which is the ratio between the number of drug targets in their proposed disease-specific genes network to the total number of interactions of the same drug in the DrugBank database. Moreover, Ozsoy et al [ 119 ] evaluated their results against ClinicalTrials.gov , which is a collection of publicly and privately funded clinical studies from around the world. The authors also performed a leave-one-out test and benchmarked their model against state-of-the-art models.…”
Section: Validation Of Computational Drug Repositioning Modelsmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that there was an error in the spelling of the name of one of the authors.…”
Section: Correctionmentioning
confidence: 99%